Pengaruh Good Corporate Governance, Ukuran Perusahaan, dan Diversitas Gender Direksi Terhadap Financial Distress (Studi Empiris pada Perusahaan Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2024) - Muhammad Ananda Putra Viansyah; Heru Suwasono (Riset Manajemen dan Akuntansi, 2025)
This study aims to determine the effect of Good Corporate Governance (GCG), company size, and board gender diversity on financial distress in property and real estate companies in Indonesia during 2020-2024. The study sample consisted of 185 data from 37 companies selected through purposive sampling from the population of property and real estate companies listed on the Indonesia Stock Exchange during 2020-2024. This study used a quantitative approach and secondary data, namely time series data, analyzed using multiple linear regression to examine the effect of good corporate governance, company size, and board gender diversity on financial distress. The results of this study differ from the research hypothesis, which stated that the independent variables have a negative effect on the dependent variable. The results indicate a positive and significant effect of institutional ownership and board gender diversity on financial distress. Meanwhile, board size and company size did not significantly influence financial distress.